PEMENUHAN KODRAT HAK-HAK PEKERJA PEREMPUAN DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN PERSPEKTIF SIYASAH DUSTURIYAH - Enggia Putri Ayuni; Sulastri Caniago (UIN Mahmud Yunus Batusangkar, 2023)
This study examines the Rights of Women Workers in Law Number 13 of 2003 concerning Employment from the Perspective of Siyasa Dusturiyah. The formulation of the problem of this research is how are the forms of legal protection for the nature of women workers according to Law Number 13 of 2003, and how is Siyasah Dusturiyah's review the nature of women workers according to Law Number 13 of 2003. This research is normative legal research or library (Library Research) The research instruments used are books, articles, journals as well as those related to Legal Protection, Manpower and Siyasah Dusturiyah. As well as the data collection technique that the authors use is a literature study carried out by reading, reviewing library materials related to legal protection of the rights of women workers and Siyasah Dusturiyah. Based on the results of this study it can be concluded that, firstly, forms of legal protection for women workers who contained in Law Number 13 of 2003 concerning Manpower which contains the rights of women workers, namely menstrual leave, maternity leave, maternity leave, and breastfeeding leave for those who have children. Second, the siyasa dusturiyah analysis of the nature of female workers in Law Number 13 of 2003 concerning Manpower that Islam has placed in an honorable and noble position in accordance with the nature and character of women equal to men in humanitarian matters and the rights granted in the Law The law regulates it and there are already provisions in the Al-Qur'an and Hadith which regulate the rights of these women.